Evidence of Oxidative Phosphorylation in Zebrafish Photoreceptor Outer Segments at Different Larval Stages. (July 2018) - Calzia, Daniela; Garbarino, Greta; Caicci, Federico; Pestarino, Mario; Manni, Lucia; Traverso, Carlo Enrico; Panfoli, Isabella; Candiani, Simona
Summary: Previous studies on purified bovine rod outer segments (OS) disks pointed to Oxidative Phosphorylation (OXPHOS) as being the most likely mechanism involved in ATP production, as yet not fully understood, to support the first phototransduction steps. Bovine and murine rod OS disks, devoid of mitochondria, would house respiratory chain complexes I to IV and ATP synthase, similar to mitochondria. Zebrafish ( Danio rerio ) is a well-suited animal model to study vertebrate embryogenesis as well as the retina, morphologically and functionally similar to its human counterpart. The present article reports fluorescence and Transmission Electron Microscopy colocalization analyses of respiratory complexes I and IV and ATP synthase with zpr3, the rod OS marker, in adult and larval zebrafish retinas. MitoTracker Deep Red 633 staining and assays of complexes I and III–IV activity suggest that those proteins are active in OS. Results show that an extramitochondrial aerobic metabolism is active in the zebrafish OS at 4 and 10 days of larval development, as well as in adults, suggesting that it is probably maintained during embryogenesis. Data support the hypothesis of an extramitochondrial aerobic metabolism in the OS of zebrafish.